1999
DOI: 10.1029/1999je001064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sterilizing doses of gamma radiation on Mars analog rocks and minerals

Abstract: Abstract. Rock and soil samples from the planet Mars are due to be returned to Earth within a decade. Martian samples initially will be tested for evidence of life and biological hazard under strict biological containment. Wider distribution of samples for organic and inorganic analysis may occur only if neither evidence of life nor hazard is detected, or if the samples are first sterilized. We subjected a range of Mars analog rocks and minerals to high doses of gamma radiation in order to determine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Though autoclaving tends to be more commonly used, some studies have found sterilization by exposure to γ-irradiation emitted by cobalt-60 to be less destructive and more effective (Bowen and Rovira, 1961;McLaren, 1969;Allen et al, 1999;;Lotrario et al, 1995;Trevors, 1996;McNamara et al, 2003;Herbert et al, 2005). Small doses of γ-irradiation are capable of sterilizing large soil samples without increasing soil temperature or pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though autoclaving tends to be more commonly used, some studies have found sterilization by exposure to γ-irradiation emitted by cobalt-60 to be less destructive and more effective (Bowen and Rovira, 1961;McLaren, 1969;Allen et al, 1999;;Lotrario et al, 1995;Trevors, 1996;McNamara et al, 2003;Herbert et al, 2005). Small doses of γ-irradiation are capable of sterilizing large soil samples without increasing soil temperature or pressure.…”
Section: Introductionmentioning
confidence: 99%
“…For determining abiotic reaction rates in mine tailings, γ-radiation was suggested as the most effective sterilization method (Herbert et al, 2005). Sterilization by γ-irradiation was recently popularized when it was suggested as a suitable technique for sterilization of Mars samples (Allen et al, 1999). Experiments showed that a dose of 30 Mrad of γirradiation caused no measurable changes in isotopic signature, chemical composition, crystallographic structure, or homogenization temperatures of fluid inclusions in rocks and minerals analogous to those found on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation levels would be in excess of the sterilizing dose of even the most radiation resistant organisms. The radiation dose received by the samples is in excess of the radiation does (10 -100 MRads) proposed as a method to sterilize samples returned from Mars (Allen et al 1999). In that respect any biological hazard is expected to be nil.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma sterilization was selected over chemical sterilization to better preserve the isotopic, chemical, and physical characteristics of the samples. The only change observed in montmorillonite clay after radiation exposure was the reversible loss of interlayer water (Allen et al 1999). Subcores were inserted into Teflon core holders (52 mm length, 33 mm inner diameter) using a mechanical cutting and loading device.…”
Section: Experimental Methodsmentioning
confidence: 99%